Interculturalism through a cognitive filter: Gilles Tremblay recomposes gamelan in Oralléluiants [1975] - Jonathan Goldman (Institut Seni Indonesia Denpasar, 2018)
In an article on the impact of gamelan music on Claude Debussy's musical language, Nicholas Cook shows Debussy's musical interpretations that navigate between viewpoints that claim that the gamelan presents